Edukasi Pengelolaan Sampah Organik Dan Anorganik Bagi Masyarakat Desa - Cep Lukman Rohmat; Dadang Sudrajat; Ikhwal Alfarizi Suherman; Intan Wangi Nur Qibti (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Waste management is an increasingly pressing environmental issue, including at the village level. This Community Partnership Program aims to provide education to villagers regarding the correct management of organic and inorganic waste. Activities include outreach on the types of waste, the negative impacts of improper waste management, methods of waste sorting at the household level, and techniques for processing organic waste into compost and utilizing inorganic waste through recycling. It is expected that, through this program, villagers can increase their awareness and knowledge about the importance of sustainable waste management, and be able to implement independent waste sorting and processing practices, thereby creating a cleaner and healthier village environment.